(untitled) (Portuguese Journal of Family Medicine and General Practice, 2018)
Introduction: Family assessment is an important component of medical evaluation, especially in Family Medicine. This case report seeks to reinforce its importance and promote its use when relevant. Case report: J. 14 years old, 9th year of schooling. J. is included in a different family environment. He has lived with his grandparents since he was 12 months old, after his father was arrested and his mother denied parental responsibilities. This situation has become particularly sensitive in his new stage of life, the adolescence. Comment: The four-step approach, suspicion and detection of a possible problem, evaluation of the family’s structural characteristics, evaluation of the family functionality, and evaluation of the social network of support and resources of the patient, allows a global evaluation of the patient and is a possible starting point for family therapy. The integrated use of family assessment in the consultation makes it possible to identify a possible family dysfunction and to promote patient empowerment on the resolution of his problems.